Platelet count and its indices as diagnostic markers of neonatal sepsis: a cross-sectional study - Goyal, Sweety; Sharma, Chandra M.; Kumar, Ravish; Mohan, Nitesh (International Journal of Contemporary Pediatrics, 2024)
Background: Neonatal sepsis is a critical condition posing a significant threat to newborns globally, particularly in developing countries. The non-specific symptoms and time-consuming traditional diagnostic methods highlight the need for rapid and reliable biomarkers. Recent studies suggest platelet count and indices such as mean platelet volume (MPV) and platelet distribution width (PDW) as potential indicators for early diagnosis of neonatal sepsis. This study aimed to assess the correlation between platelet count and its indices and neonatal sepsis. Methods: A hospital-based cross- sectional study was conducted at NICU of tertiary care hospital involving 80 neonates with suspected sepsis. Platelet count, PDW, and MPV were measured and correlated with neonatal sepsis. Statistical analyses were performed using SPSS software, with a significance set at p<0.05. Results: Of the 80 neonates studied, 22.5% exhibited thrombocytopenia. There was a noteworthy inverse relationship discovered between platelet count and sepsis, while MPV and PDW were higher. Gram-negative organisms were the most common cause of sepsis, out of which E. Coli (63.64%) was the most common. Conclusions: The study confirmed a significant association between platelet count and indices with neonatal sepsis. Platelet count, MPV, and PDW can serve as effective, rapid diagnostic markers, potentially improving early detection and outcomes in neonatal sepsis.